Incidence of atrial fibrillation in a population with impaired glucose tolerance: the contribution of glucose metabolism and other risk factors. A post hoc analysis of the Nateglinide and Valsartan in Impaired Glucose Tolerance Outcomes Research trial. - Latini, R; Staszewsky, L; Sun, J; Bethel, M; Disertori, M; Haffner, S; Holman, R; Chang, F; Giles, T; Maggioni, A; Rutten, G; Standl, E; et al. (2013)
BACKGROUND: The role of dysglycemia as an additional risk factor for atrial fibrillation (AF) is controversial. Therefore, it was of interest to assess risk factors for incident AF in a large, representative population of patients with cardiovascular risk factors and impaired glucose tolerance but not overt diabetes in NAVIGATOR. METHODS: Predictors of incident AF were analyzed in 8,943 patients without AF at baseline by Cox proportional hazards regression. Study treatments (valsartan vs no valsartan and nateglinide vs no nateglinide) and the time-dependent covariate for progression to type 2 diabetes mellitus were added separately to the model. RESULTS: The median age of the 8,943 patients included in the present analysis of the NAVIGATOR trial was 63 years. Half of those patients were men, 6,922 (77.4%) had a history of hypertension, and 255 (2.9%) had heart failure. The median glycated hemoglobin was 6%. During the study, 613 of the 8,943 patients without AF at baseline presented with at least 1 episode of AF (6.9% 5-year incidence). Besides established predictors of incident AF, a 1 mmol/L increment of baseline fasting glucose, but not progression to diabetes, was found to be associated with a 33% increased risk of incident AF. Neither valsartan nor nateglinide affected AF incidence. CONCLUSIONS: In a trial population with impaired glucose tolerance, fasting plasma glucose and well-known risk factors (age, hypertension, and elevated body weight), but not progression to diabetes, predict risk of AF.